Viability of Frozen-Thawed Epididymal Sperm of Garut Ram - MUHAMMAD RIZAL; HERDIS HERDIS (HAYATI Journal of Biosciences, 2005)
Sperm collected from cauda epididymis is a source of male gametes. The purposes of this study was to evaluate an quality of frozen-thawed sperm of garut ram which was collected from cauda epididymis and cryopreserved with modified Tris extender, i.e: Tris extender (control, KT), Tris extender + 60 mM lactose (LS), and Tris extender + 60 mM lactose + 0.05% glutathione (GL). Quality of collected sperm including concentration, motility, live sperm, abnormality, cytoplasmic droplet, intact acrosomal cap (IAC), and intact plasma membrane (IPM) were evaluated. Results showed that mean of sperm concentration, percentages of motility, live sperm, abnormality, cytoplasmic droplet, IAC, and IPM of fresh epididymal sperm were 13,993.33 million/ml, 70.83, 82.83, 10.83, 8.5, 85.83, and 81.33%, respectively. Sperm quality after equilibration for LS and GL were significantly (P